Investigation of primary health care service delivery models used in allied health practice in rural and remote areas of Australia: a systematic review - Alison Brown; Alexandra Cant; Rebecca Wolfgang; Robyn Ramsden; Susan Heaney; Leanne J. Brown (BMC Health Services Research)
Abstract Introduction In Australia, access to primary health care (PHC) services is limited in comparison to major cities. Allied health professionals play a pivotal role in providing necessary PHC in rural and remote areas. However, there is limited evidence about the most effective allied health specific PHC models of care that can be utilised in these settings. The aim of this review was to describe the PHC models used by allied health professionals in rural and remote areas of Australia and report on their impact and effectiveness in improving care. Methods A search of five databases (MEDLINE, Embase, CINAHL, PsychINFO and Informit Health) was undertaken. Articles were included that related to a refined list of allied health professions that specifically work in PHC settings, these included: dietetics; occupational therapy; physiotherapy; psychology; speech pathology; social work; podiatry; exercise physiology; pharmacy; optometry; and audiology. Articles with a focus on a PHC model of service delivery in a rural or remote area were included. The effectiveness and impact of these models was examined. The Mixed Methods Appraisal Tool was used to assess the quality of the included articles. Results A total of 57 articles met the inclusion criteria, from an initial 1864 unique citations sourced from searches. Of the 57 articles, 22 studies were in the Australian context and were included in this paper. The outcome measures typically included improving access to services, however minimal impact or effectiveness data was reported. Studies were categorised into an existing typology of PHC models: integrated services (n = 9); outreach services (n = 3); virtual outreach services (n = 4); discrete services (n = 4); with an additional model being health promotion (n = 5). Conclusion A range of PHC models were used by allied health disciplines in rural and remote areas of Australia. These models focused on improving access to allied health services in primary care settings to address health inequities faced. Given the limited reporting of the impact of these services, it is recommended that rigorous evaluations of existing allied health models are undertaken. There is a gap in the literature regarding the models of service delivery being used by allied health professionals in non-metropolitan areas.